Profil Resiliensi Mahasiswa Broken Home (Studi pada Mahasiswa BK Universitas PGRI Sumatera Barat) - Dinie Eka Putri; Rila Rahma Mulyani; Besti Nora Dwi Putri (Institut Agama Islam Negeri Curup, 2023)
This research is motivated by the observation that students from broken homes often exhibit avoidant behavior when discussing their family, struggle to regulate their emotions, including crying, when talking about their family, and frequently withdraw from social situations.. This study aims to determine the level of resilience in students broken home seen from; 1) emotion regulation, 2) impulse control, 3) empathy, 4) a optimism, and 5) problem analysis that contribute to student resilience profiles. This study used a quantitative descriptive method with a research population of 60 students selected by the method total sampling with the number of samples taken 60 students. The instrument used is a questionnaire. The aspects of resilience studied include emotion regulation, impulse control, optimism, empathy, and problem analysis skills. Data were analyzed descriptively quantitatively to describe the resilience profile of BK students with different backgrounds broken home. The results of the analysis show that the profile of student resilience is based on background broken home in the PGRI University West Sumatra BK study program are in the medium category. Here are the details; 1) the emotion regulation aspect is in the medium category, 2) the impulse control aspect is in the high category, 3) the empathy aspect is in the medium category, 4) the optimistic aspect is in the moderate category, 5) the problem analysis aspect is in the medium category. Even so, all aspects of resilience have variations in students who have family backgrounds broken home. This research can provide information about the resilience profile description, and this description can be a reference in improving student resilience profiles as well as being a benchmark in developing student resilience profiles broken home become even better.Keywords: Student Broken home, Resilience